TEACHERS’ INSTRUCTIONAL STRATEGIES AND STUDENTS’ PERCEPTION TOWARD ENGLISH LEARNING IN THE TAHFIDZ CLASS AT MIN 2 MOJOKERTO - Rama Bintang Hendrianto; Aida Fitrianah Zen; Rica Rachmania (JETS, English Department of University of Uluwiyah Mojokerto, 2025)
This study describes the teaching strategies used by the English teacher and the students’ perception of English learning in the Tahfidz class at MIN 2 Mojokerto. The research used a qualitative descriptive method with one English teacher and 28 students as participants. Data were collected through observation, interview, and documentation. The results show that the teacher used group discussion, repetition, direct explanation, translation, and question–answer strategies. These methods were chosen to make learning easier for students whose main focus is Qur’an memorization. Students’ perception was both positive and negative. Most students liked interactive activities such as group work and learning new words, but some felt English was still difficult and sometimes hard to focus on. In conclusion, interactive and group-based strategies are effective for Tahfidz students, but more help is needed when lessons rely on direct explanation.